(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2011)
This article presents the results of quasi-experimental research design with pretest-post test control group to assess the ability of the mathematical representation student’s using experience-based learning model of type Knisley-Mulyana. The study was conducted on student of junior high school. Two classes were randomly selected to serve as the study sample. Students in experimental class get Knisley-Mulyana learning, while students in the control class get the conventional learning. There are two main instruments used, namely the ability test of mathematical representation and questionnaires. Questionnaires used to evaluate the response of students towards learning with Knisley-Mulyana model. The Results showed that students who acquire the learning of mathematics by using Knisley-Mulyana model provide a achievement of the mathematical representation capability better than students who received conventional learning. Viewed from the mathematical skills, students in the high group and low group with Knisley-Mulyana learning achieve their ability of mathematical representation better than students in the same group who received conventional learning. In other words the most effective group of students in the application of Knisley-Mulyana learning is a high and low groups. In addition, students responded well to learning by using Knisley-Mulyana model.